2012
DOI: 10.1111/j.1749-6632.2012.06750.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and cancer risk: evidence, mechanisms, and recommendations

Abstract: Obesity, a growing health problem worldwide, has been associated with the metabolic syndrome, diabetes, cardiovascular disease, hypertension, and other chronic diseases. Recently, the obesity–cancer link has received much attention. Epidemiological studies have shown that obesity is also associated with increased risk of several cancer types, including colon, breast, endometrium, liver, kidney, esophagus, gastric, pancreatic, gallbladder, and leukemia, and can also lead to poorer treatment and increased cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
294
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(320 citation statements)
references
References 53 publications
7
294
0
7
Order By: Relevance
“…After reviewing several studies, Crimmins et al (Crimmins and Martin, 2007) reported that rs1342387 was the only single nucleotide polymorphism (SNP) of adiponectin receptor 1 which was significantly associated with HOMA-IR as a measure of insulin resistance. Present studies had shown that obesity and insulin resistance were risk factors of kinds of cancers (Inoue and Tsugane, 2012;Vucenik and Stains, 2012). And Insulin levels were shown to be correlated with the expression of adiponectin receptors (Tsuchida et al, 2004), which could be downregulated by obesity and in turn lead to insulin resistance (Ouchi et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…After reviewing several studies, Crimmins et al (Crimmins and Martin, 2007) reported that rs1342387 was the only single nucleotide polymorphism (SNP) of adiponectin receptor 1 which was significantly associated with HOMA-IR as a measure of insulin resistance. Present studies had shown that obesity and insulin resistance were risk factors of kinds of cancers (Inoue and Tsugane, 2012;Vucenik and Stains, 2012). And Insulin levels were shown to be correlated with the expression of adiponectin receptors (Tsuchida et al, 2004), which could be downregulated by obesity and in turn lead to insulin resistance (Ouchi et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…In 2008, an estimated 12.7 million new cancer cases and 7.6 million cancer deaths occurred all over the world (Ferlay et al, 2010), and in the same year, about 1.46 billion adults were overweight worldwide, of whom estimated 500 million adults were obese (Finucane et al, 2011). Epidemiological studies had established that increasing of BMI and excess body weight were risk factors for some cancers, such as colorectal cancer, prostate cancer and renal cancer, which were called obesity-related cancers (Renehan et al, 2008;Vucenik and Stains, 2012). Recent studies had revealed that adiponectin, the most abundant adiposetissue protein, was a key player in the development and progression of obesity-related cancers (Barb et al, 2007;Paz-Filho et al, 2011;Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…No mesmo sentido, essa condição se associa ao aumento da probabilidade de desenvolver doenças cardiovasculares, síndrome metabólica, diabetes, hipertensão, câncer e outras doenças crônicas e ortopédicas 39 . Nesse contexto, o exercício físico a lonFigura 2 -Forest plots dos efeitos para interveção HIIT e CONT nos desfechos a) massa corporal total (MCT), b) percentual de gordura (%G); HIIT-treinamento intervalado de alta intensidade; CONT -treinamento contínuo; IV -inverso da variânça; IC -intervalo de confiança; DP -desvio padrão.…”
Section: Discussionunclassified
“…It is known that obese patients suffer from four dietary and lifestyle behavioral changes including increased dietary energy intake, increased intake of saturated fats, decreased intake of vegetables and fruits and reduced physical activity levels [7]. Besides, four metabolic changes occur inside their bodies and contribute to the development of cancer: oxidative stress and the damage it causes to DNA; hormonal stress represented by an increased anabolic hormones like insulin, steroid sex hormones and insulin-like growth factor-1 (IGF-I); increased level of inflammatory intermediate components; and increase in other biological factors linked to cancer such as C-Reactive protein (CRP) [8].…”
Section: Obesity-cancer Connectionmentioning
confidence: 99%